Criticism of Arab Reason: Reading Muhammad Abid Al-Jabiri's Path of Knowledge - Saidil Yusron; Mohammad Muslih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The central theme of the idea of renewal of thought in Islam lies in the key word I'aadatul Islam; That is the desire of the Muslim community to restore the role of the Islamic world in the global arena of world civilization. If Muhammad Abduh made Tajdid Al-Fahm (Renewing the Understanding of Islam) as a key word in his thought pattern, Rashid Rida had the concept of Tathbiq Al-Shari'ah or Tathbiq Qanun Al-Shar'iyyah, then, contemporary Islamic thinkers – Hasan Hanafi, Muhammad Arkoun and 'Abid Al-Jabiri – for example prefer to focus on the reconstruction of the understanding of tradition and criticism of the reason or system of thinking of Muslims. Al-Jabiri's concern for the decline of the Arabs and the failure of the Islamic revival in general, prompted him to examine the causes that led to this failure. The main problem that has not been resolved is how to respond and position heritage (turast) with the flow of modernization. The study should take into account the thoughts of the owner of the dal text. Studies must take into account the thoughts of the owner of the text in the context of its historical time, and reveal the ideological function desired by the thought intended in the realm of general knowledge to which it belongs. Thus, making the text contemporary for itself means separating it (fashl) from us and relating it (rabth) to the reality it produces.